IMPROVING STUDENTS’ WRITING ABILITY THROUGH PROJECT BASED-LEARNING USING VISUAL MEDIA - Iis Harisma; Ghina Ilmiah; Yana Yana (PROJECT (Professional Journal of English Education), 2019)
The aim of this study is to know the improvement of students’ writing ability through Project based-learning using visual media in recount text at X Grades of students’ Vocational High School in Cimahi. This study was Quantitative design, the sample of research consisted of 30 students. The instrument used in this research was written test. The written test was applied in pretest and posttest. The writing test was administrated as the instrument of the research. The result shown that the students’ total score of pretest was 176, and then total score of posttest was 2222. It means that students’ score increased. Then the data were analyzed using statistical formula of t-test computation The data were analyzed by using t-test as the significant level of p<0.05 through SPSS version 15.0. Based on t-measure analysis show that T-score (9,589) ˃ T-table 5% (2, 045).  It means that was significant so the Null Hypothesis (Ho) was rejected. It means that Project based- Learning using Visual Media has significant effect in improving students’ writing ability.